Clinical outcomes with first-line chemotherapy versus endocrine therapy for adjuvant endocrine therapy-resistant metastatic breast cancer - Shao, Bin; Yang, Yanlian; Qu, Jinrong; Li, Huiping; Song, Guohong; Di, Lijun; Jiang, Hanfang; Yan, Ying; Wang, Huan; Liu, Xiaoran; Wang, Jing; Kong, Weiyao (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Endocrine therapy resistance (ETR) is a great obstacle in the treatment of estrogen receptor-positive (ER+)/human epidermal growth factor receptor 2-negative (HER2−) breast cancer. Patients with ETR have significantly decreased clinical benefit from endocrine therapy (ET). Therefore, it is quite important to find the clinicopathological factors that affect the outcome of patients with ETR in clinical practice. Methods: We screened 405 consecutive ER+/HER2− metastatic breast cancer (MBC) patients who were treated from 2013–2015 in our hospital. Patients with ETR (defined as relapse during adjuvant ET or within 12 months after completing adjuvant ET) were selected to explore the clinicopathological factors affecting the objective response rate (ORR) and progression-free survival (PFS). Results: We included 135 patients in the study. Chemotherapy (CT) was administered to 96 patients and ET to 39 patients as first-line treatment. Patients with liver or visceral metastasis received CT significantly more frequently than ET (P=0.001, 0.001). There was no significant difference in median PFS between the two groups (ET: 11.8 months, CT: 12.0 months, P=0.931, HR =1.029). However, patients with more than two metastatic sites had a shorter PFS than patients with less than or equal to two metastatic sites (7.5 vs. 14.5 months, P=0.031, HR =1.714). When patients on CT were further stratified, those who received ET as maintenance therapy had a longer PFS (14.3 months) compared with those that did not (7.5 months) (P=0.003). Conclusions: ET and CT were both appropriate treatments for patients with ETR. Maintenance ET was a good choice for ER+/HER2− patients.